Renitrosylation of banked human red blood cells improves deformability and reduces adhesivity. Issue 10 (22nd June 2015) - Riccio, Daniel A.; Zhu, Hongmei; Foster, Matthew W.; Huang, Brendan; Hofmann, Christina L.; Palmer, Gregory M.; McMahon, Tim J.
<x xml:space="preserve">Abstract</x> BACKGROUND Transfusion of red blood cells (RBCs) is a frequent health care practice. However, unfavorable consequences may occur from transfusions of stored RBCs and are associated with RBC changes during storage. Loss of S‐nitrosohemoglobin (SNO‐Hb) and other S‐nitrosothiols (SNOs) during storage is implicated as a detriment to transfusion efficacy. It was hypothesized that restoring SNOs within banked RBCs would improve RBC functions relevant to successful transfusion outcomes, namely, increased deformability and decreased adhesivity. STUDY DESIGN AND METHODS Stored human RBCs were incubated with nitric oxide (NO) donors PROLI/NO and DEA/NO (disodium 1‐[2‐(carboxylato)‐pyrrolidin‐1‐yl]diazen‐1‐ium‐1, 2‐diolate and diethylammonium (Z)‐1‐(N, N‐diethylamino)diazen‐1‐ium‐1, 2‐diolate) under varying experimental conditions (e.g., aerobic/anaerobic incubation, NO donor to RBC ratio). SNO restoration was evaluated in vitro and in vivo as a means to improve RBC function after storage. RESULTS Incubation of RBCs with the NO donors resulted in 10‐fold greater levels of SNO‐Hb versus untreated control or sham RBCs, with significantly higher Hb‐bound NO yields from an NO dose delivered by DEA/NO. RBC incubation with DEA/NO at a stoichiometry of 1:62.5 NO:Hb significantly increased RBC deformabilty and reduced adhesion to cultured endothelial cells. RBC incubation with DEA/NO also increased S‐nitrosylation of RBC cytoskeletal and membrane proteins, including the β‐spectrin chain. Renitrosylation attenuated both RBC sequestration in the lung and the mild blood oxygen saturation impairments seen with banked RBCs in a mouse model of transfusion. CONCLUSIONS RBC renitrosylation using NO donors has promise for correcting deficient properties (e.g., adhesivity, rigidity, and SNO loss) of banked RBCs and in turn improving transfusion outcomes.